2018
DOI: 10.1182/bloodadvances.2018016261
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt hematoporphyrin inhibits CLEC-2–podoplanin interaction, tumor metastasis, and arterial/venous thrombosis in mice

Abstract: The platelet activation receptor C-type lectin-like receptor 2 (CLEC-2) interacts with podoplanin on the surface of certain types of tumor cells, and this interaction facilitates tumor metastasis. CLEC-2 is also involved in thrombus formation and its stabilization. Because CLEC-2-depleted mice are protected from experimental lung metastasis and thrombus formation and do not show increased bleeding time, CLEC-2 may serve as a good target for antimetastatic or antithrombotic drugs. We screened 6770 compounds for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 33 publications
(58 reference statements)
0
61
0
Order By: Relevance
“…Currently, the development of metal complexes with nonplatinum central atoms including ruthenium [11], gold [12], silver [13], copper [14], zinc [15], Manganese [16], nickel [17], iridium [18] and cobalt [19] has been one of the hottest emerging areas of anticancer drug research. Among these, carbonyl cobalt complex has strong properties of cancer prevention including tumour growth/metastasis suppression [20], antiproliferative [21], DNA cleavage [22], apoptotic induction [23] and autophagy [8], which was more active than cisplatin on the human breast tumour cell lines (MCF-7 and MDA-MB-231) [24,25] and ovarian cancer cells (SKOV3/ DDP) [26]. With the concept of carbonyl metal CO-releasing molecules (CORMs) appearing, the anti-inflammatory effects were found through liberating CO to inhibit nitrite content [27].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the development of metal complexes with nonplatinum central atoms including ruthenium [11], gold [12], silver [13], copper [14], zinc [15], Manganese [16], nickel [17], iridium [18] and cobalt [19] has been one of the hottest emerging areas of anticancer drug research. Among these, carbonyl cobalt complex has strong properties of cancer prevention including tumour growth/metastasis suppression [20], antiproliferative [21], DNA cleavage [22], apoptotic induction [23] and autophagy [8], which was more active than cisplatin on the human breast tumour cell lines (MCF-7 and MDA-MB-231) [24,25] and ovarian cancer cells (SKOV3/ DDP) [26]. With the concept of carbonyl metal CO-releasing molecules (CORMs) appearing, the anti-inflammatory effects were found through liberating CO to inhibit nitrite content [27].…”
Section: Introductionmentioning
confidence: 99%
“…( 35 ) We recently reported that cobalt hematoporphyrin could selectively inhibit the CLEC‐2–podoplanin interaction without affecting the responsiveness to other platelet agonists and bleeding time whereas cobalt hematoporphyrin could reduce arterial and deep vein thrombosis. ( 36 ) Consequently, platelet CLEC‐2 may be a more promising and safer treatment target than podoplanin for patients with osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, CLEC‐2 plays a critical role in embryonic development, facilitating blood‐lymphatic separation, cerebrovascular patterning and integrity, lymph node and lung development, as well as platelet formation and the maintenance of hematopoietic stem cells in the bone marrow . In cancer, the interaction of CLEC‐2 with podoplanin‐expressing tumour cells promotes angiogenesis, tumour growth and metastasis, and may represent a target for therapy, if the side‐effects on the haemostatic functions of the receptor can be overcome . In contrast, expression of CLEC‐2 on some cancer cells, such as gastric cancer cells, may be protective .…”
Section: Introductionmentioning
confidence: 99%